2019
DOI: 10.1103/physrevresearch.1.032003
|View full text |Cite
|
Sign up to set email alerts
|

Long-time persistence of hydrodynamic memory boosts microparticle transport

Abstract: In a viscous fluid, the past motion of an accelerating particle is retained as an imprint on the vorticity field, which decays slowly as t −3/2 . At low Reynolds number, the Basset-Boussinesq-Oseen (BBO) equation correctly describes nonuniform particle motion, capturing hydrodynamic memory effects associated with this slow algebraic decay. Using the BBO equation, we numerically simulate driven single-particle transport to show that memory effects persist indefinitely under rather general driving conditions. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 123 publications
1
5
0
Order By: Relevance
“…It remains to be seen whether such enhancements in the rate are experimentally observable and can be traced back to backflow effects. However, their occurrence appears to be consistent with the enhancements in transport properties that have been seen in the simulations of particle motion in tilted washboard potentials alluded to in the Introduction and with the finding that hydrodynamic memory effects can persist indefinitely under fairly general driving conditions . The physical basis for these different phenomena is not entirely clear, but a lowering of the particle’s effective friction coefficient may be one possibility …”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…It remains to be seen whether such enhancements in the rate are experimentally observable and can be traced back to backflow effects. However, their occurrence appears to be consistent with the enhancements in transport properties that have been seen in the simulations of particle motion in tilted washboard potentials alluded to in the Introduction and with the finding that hydrodynamic memory effects can persist indefinitely under fairly general driving conditions . The physical basis for these different phenomena is not entirely clear, but a lowering of the particle’s effective friction coefficient may be one possibility …”
Section: Resultssupporting
confidence: 78%
“…However, their occurrence appears to be consistent with the enhancements in transport properties that have been seen in the simulations of particle motion in tilted washboard potentials alluded to in the Introduction 25−28 and with the finding that hydrodynamic memory effects can persist indefinitely under fairly general driving conditions. 27 The physical basis for these different phenomena is not entirely clear, but a lowering of the particle's effective friction coefficient may be one possibility. 27 The present treatment of backflow effects on barrier crossing has been restricted to the case of Markovian friction [for which K(t) = 2δ(t) and the Stokes force F S (t) in eq 3 is just −ζv(t)], but it can be generalized to consider nonlocal friction as well, corresponding to F S (t)= −ζ ∫ 0 t dt′K(t − t′)x(t′), if it is accepted, as argued in ref 41, that hydrodynamic and frictional memory are related as…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…149,150 Thus, they showed that the Basset−Boussinesq equation is also applicable in the microscopic regime, with parameters that can be directly derived from the memory function. 61 Seyler and Presse 151,152 investigated the influence of this "Basset history force" on the motion of microspheres in oscillatory flow and a periodic potential. They showed that hydrodynamic memory significantly enhances the mobility of microspheres and helps them to escape potential wells in which they would otherwise remain trapped for much longer times.…”
Section: Physical Impact Of Memorymentioning
confidence: 99%